COMMUNICATION EFFECTIVENESS MODEL FOR VACCINATION PARTICIPATION IN SEMARANG CITY - PERTIWI PUTRI, ARFIKA; Budiono, Taruna; Triyomo, Agus (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2024)
The vaccination program is an important effort to combat the pandemic, starting from the initial doses of vaccines to booster shots. However, the program has not yet achieved its intended target. In August, the booster vaccination coverage in Semarang City was only 53%, falling short of the desired 80% (KompasTV, 2022). Therefore, there is a pressing need for persuasive measures to enhance knowledge, awareness, and decision- making regarding vaccination. This study aims to identify an effective model of vaccine persuasion for public communication in Semarang City. It is an exploratory study that applies the Elaboration Likelihood Model (ELM) theory and the diffusion of innovations, involving a sample of 100 respondents. The collected data was analyzed using PLS 3.0. The results reveal that persuasion using different lines of thought (central route and peripheral route) leads to distinct stages of innovation diffusion. Both new media and traditional media are considered suitable platforms for vaccine persuasion, provided they incorporate key elements such as high-quality information, credible sources, accessibility, well-structured messages, and interactivity.